Metabolomics : a new perspective in pharmaceutical industries - Khatib, Alfi (2018)
Quality control in pharmaceutical industries requires a fast and cheap method but at the same time accurate and robust. The nature of the product produced by pharmaceutical industries may cover multi-components especially the nature based-industry such as herbal products. Thus, it needs a holistic analytical method that consider whole metabolites in the sample. Different instrumental platforms should be used such as nuclear magnetic resonance, mass-spectrometer, and infrared spectroscopy because no single instrument is able to detect whole range of metabolites. This presentation explain some examples of metabolomics application in pharmaceutical industries based on multi-platform instruments.